The Relationships Among Extrinsic Cues, Perceived Quality, Perceived Sacrifice and Perceived Value: A Cross National Study - Liu, Yang (Auckland University of Technology, 2005)
Consumer perceived value is an important concept in marketing and plays a significant role in purchase decision-making. Consumer perceived value can be markedly influenced by product cues. The current research investigates the impact of extrinsic cues (country-of-origin, brand name, store name and price) on consumer perception of product quality, sacrifice and value developed by Teas and Agarwal (2000). Since little research has examined the generalisability of Teas and Agarwal’s (2000) work in less economically developed countries, this research is conducted in a Chinese population. The relationships among four manipulated extrinsic cues, perceived sacrifice, quality and value are tested. Since Teas and Agarwal (2000) did not investigate the mediation affects of perceived sacrifice in the relationship between perceived quality and perceived value, this will be also explored as an additional study for this paper. Thus, the current research expands on previous work on perceived customer value by examining the mediation affects. After the conceptual model of Teas and Agarwal (2000) has been examined, the findings support hypothesized linkages between each of the four extrinsic cues and perceived quality, price and perceived quality, perceived quality and perceived value, perceived sacrifice and perceived value. The results show that perceived sacrifice mediates the relationship between perceived quality and value. The results also indicate that the linkages between the extrinsic cues and perceived value are mediated by perceived quality but are not mediated by perceived sacrifice. Although the results show that one hypothesized mediation affect is not supported, the overall structure of the model is supported across countries. The findings are similar to the study of Teas and Agarwal (2000) which suggests that Chinese and Western consumer behaviours are alike in most situations. For example, brand building is a critical cue to the desired success because it can promote perceptions from both quality and value perspectives. However, this research found that Chinese consumers use product evaluation cues in a different way from Western consumers. The major difference is that, if the price is lower than the reasonable average price-level, Chinese consumers may consider the product to be a big bargain with perceived high quality. This may suggest that marketing managers can use discount and price promotions in China. Therefore, discussions and managerial implications of this research provide advice for managers to formulate appropriate strategies.
Keywords: Brand name products; Consumer behavior -- China